PEMETAAN JALUR EVAKUASI TSUNAMI DI KOTA BENGKULU BERBASIS ARCGIS HUB - Yehezkiel Santoso; Hanna Prillysca Chernovita (Universitas Muhammadiyah Gorontalo, 2022)
Bengkulu city is an area facing the Indo-Australian tectonic plate, resulting in frequent earthquakes above 5 on the Richter scale and triggering the potential for a tsunami. This research was conducted in 9 sub-districts of Bengkulu City and aimed to design a geographic information system for pre-disaster mitigation that provides a visual form of tsunami exposure and allows users to carry out analysis independently route point locations to evacuation sites. The method used is overlaying and scoring the map of distance from the coastline, distance from the river, elevation and slope, so as to obtain an exposure map that can be used as a reference in conducting network analyst closet facility. The data that has been analyzed is then uploaded to ArcGIS Online to be customized and configured as WebGIS. The results showed that there were 7 sub-districts that had high levels of exposure and had routed 58 incident points to 17 temporary evacuation sites.